Polypharmacy and drug-drug interactions among older and younger male prisoners in Switzerland. Issue 3 (29th August 2019) - Annaheim, Beatrice; Wangmo, Tenzin; Bretschneider, Wiebke; Handtke, Violet; Elger, Bernice S.; Belardi, Angelo; Meyer, Andrea H.; Hösli, Raphael; Lutters, Monika
Abstract : Purpose: The purpose of this paper is to determine the prevalence of polypharmacy and drug–drug interactions (DDIs) in older and younger prisoners, and compared if age group is associated with risks of polypharmacy and DDIs. Design/methodology/approach: For 380 prisoners from Switzerland (190 were 49 years and younger; 190 were 50 years and older), data concerning their medication use were gathered. MediQ identified if interactions of two or more substances could lead to potentially adverse DDI. Data were analysed using descriptive statistics and generalised linear mixed models. Findings: On average, older prisoners took 3.8 medications, while younger prisoners took 2.1 medications. Number of medications taken on one reference day was higher by a factor of 2.4 for older prisoners when compared to younger prisoners ( p = 0.002). The odds of polypharmacy was significantly higher for older than for younger prisoners (>=5 medications: odds ratio = 5.52, p = 0.035). Age group analysis indicated that for potentially adverse DDI there was no significant difference (odds ratio = 0.94; p = 0.879). However, when controlling for the number of medication, the risk of adverse DDI was higher in younger than older prisoners, but the result was not significant. Originality/value: Older prisoners are at a higher risk of polypharmacy but their risk for potentially adverse DDI is not significantly different from that of younger prisoners. Special clinical attention must be given to older prisoners who are at risk for polypharmacy. Careful medication management is also important for younger prisoners who are at risk of very complex drug therapies.